Analisis Distribusi Hukum Ekonomi di Indonsia dalam Perekonomian Masyarakat Serta Efektivitas Kebijakan Hukum Ekonomi di Indonesia - Zahra Sabrina Anggiani Putri; Muhammad Iqbal Firmansyah; Farahdinny Siswajanthy (Sharia Journal and Education Center Publishing, 2024)
Society and law are intertwined in regulating all aspects of human life, one of which is the economic aspect. Economic law is a law that regulates the running of a country's economy which not only focuses on economic development but also equality in the goal of social welfare. This is achieved by issuing laws that regulate all forms of economics or those related to the economy. One of the problems that the government really pays attention to is the level of unemployment which must be emphasized in order to achieve a prosperous society. Not only that, the government also provides policies to business actors who carry out monopolies because it can have a negative impact on other business actors and consumers. By dominating the market and not competing in a healthy manner, it can also cause financial losses to the country. This policy certainly provides convenience for all parties in carrying out economic activities